Physiological Responses and Bout Analysis in Elite Kickboxers During International K1 Competitions - Rydzik, Łukasz; Maciejczyk, Marcin; Czarny, Wojciech; Kędra, Andzej; Ambroży, Tadeusz (Frontiers in Physiology, 2021)
Background: Kickboxing is a combat sport with various forms of competition. Kickboxing according to the K1 rules is one of the most interesting and quickly developing forms of kickboxing. According to the K1 rules, it is possible to use a variety of techniques with great force. The aim of this study was to investigate the physiological responses during a real sports fight and to perform a technical and tactical analysis of the kickboxing bout according to the K1 rules. Methods: This study was conducted during two cycles of the international kickboxing league according to the K1 rules in a group of 15 elite athletes. The indicators of technical and tactical training were evaluated in real sports bout. Blood lactate (LA) levels and heart rate (HR) were measured during and after the bout. Results: The efficiency of the attack was on average 59.3 ± 2.7, its effectiveness was 50.3 ± 10.01, and its activeness was 112.3 ± 29. The peak LA concentration was 14.6 ± 1.9 mmol/L. LA concentration did not decrease to baseline after 20 min of recovery. Conclusion: A kickboxing bout was found to induce strong physiological stress for the participants. Reported HR and LA concentration show that the intensity of the fight was close to maximal, and anaerobic metabolism played an important role during a fight.